(untitled) (Journal of Medicine, 2022)
Background: Pseudomonas aeruginosa is a notorious gram-negative bacterium that has become a globalpublic health concern owing to the emergence of multi- and pandrug-resistant strains. This study sought todetermine the antibiotic susceptibility profile of P. aeruginosa in a tertiary medical center from Malaysia. Materials and Methods: Each isolate’s identity was confirmed using the VITEK 2 GN kit, and subjectedto antibiotic susceptibility testing using the VITEK 2 AST-N374 card (for testing against piperacillintazobactam,ceftazidime, cefepime, imipenem, meropenem, amikacin, gentamicin and ciprofloxacin) andEtest strips (for testing against doripenem and polymyxin B). Isolates which were not susceptible to >1carbapenem were tested for carbapenemase production using the modified carbapenem inactivationMethod (mCIM). Results: Out of 102 isolates studied, 64 (62.7%) were fully susceptible to all the antibiotics tested.Twenty-six (25.5%) were resistant to >1 antibiotic from >2 antibiotic classes, and 21 (20.6%) wereresistant to >1 antibiotic from >3 classes. Susceptibility was highest with polymyxin B (100%) and lowestwith piperacillin-tazobactam (64.7%). Carbapenem susceptibility was between 78.4% to 81.4%. Out of 22isolates which were not susceptible to >1 carbapenem, 18 (81.8%) were not susceptible to all threecarbapenems. Conclusion: More than half of our P. aeruginosa isolates were fully susceptible to all the anti-pseudomonalantibiotics tested. Multidrug-resistant strains accounted for between 20% to 25% of all our P. aeruginosaisolates. Through mCIM testing, carbapenemase production did not appear to be the dominant resistancemechanism. J MEDICINE 2022; 23: 54-60